VD_FINDINFO Arrêt / 2012 / 511 vom 22. Mai 2012 - VD Tribunal cantonal (2012)
COMMUNICATION AVEC LE DÉFENSEUR, VISITE, CURATELLE ÉDUCATIVE | 273 al. 1 CC, 308 al. 1 CC, 420 al. 2 CC, 405 CPC, 489 CPC, 174 al. 2 CDPJ